2023
DOI: 10.3390/medicina59061066
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Efficacy of Morning Light Therapy for Adults with Insomnia: A Pilot, Randomized, Open-Label, Two-Arm Study

Jihyun Yoon,
Seokjae Heo,
Hyangkyu Lee
et al.

Abstract: Background and Objectives: Light therapy (LT) is used as an adjunctive treatment for sleep problems. This study evaluates the impact of LT on sleep quality and sleep-related parameters in patients with sleep disorders. Materials and Methods: We performed a pilot, randomized, open-label clinical trial. Fourteen patients aged 20–60 years with insomnia were randomized into the control and LT groups (1:1 ratio). The LT group was instructed to use a device that provides bright LT (6000 K, 380 lux, wavelength 480 nm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Based on the pilot study we previously conducted, we calculated the necessary sample size 12 . We determined the necessary total sample size of 40 individuals by applying an alpha 0.05, effect size of 0.53, and power of 0.9, based on the mean ± standard deviation (SD) difference values (-1.286 ± 2.425) observed before and after using the Epworth Sleepiness Scale (ESS) in the group for which conventional light was used.…”
Section: Sample Size Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the pilot study we previously conducted, we calculated the necessary sample size 12 . We determined the necessary total sample size of 40 individuals by applying an alpha 0.05, effect size of 0.53, and power of 0.9, based on the mean ± standard deviation (SD) difference values (-1.286 ± 2.425) observed before and after using the Epworth Sleepiness Scale (ESS) in the group for which conventional light was used.…”
Section: Sample Size Calculationmentioning
confidence: 99%
“…LT can be tailored in terms of intensity and correlated color temperature (CCT) for the management of sleep problems 4,12,13 . Research, including our own 4,12,13 , has demonstrated that light with a wavelength of approximately 460 nm can signi cantly modulate melatonin suppression, thereby facilitating sleep regulation. The role of CCT in LT, in uencing melatonin levels and circadian rhythms, is increasingly recognized as a crucial factor in sleep therapy 14 .…”
Section: Introductionmentioning
confidence: 99%
“…LT can be tailored in terms of intensity and correlated color temperature (CCT) for the management of sleep problems [4,15,16]. Research, including our own [4,15,16], has demonstrated that light with a wavelength of approximately 460 nm can significantly modulate melatonin suppression, thereby facilitating sleep regulation. The role of CCT in LT, influencing melatonin levels and circadian rhythms, is increasingly recognized as a crucial factor in sleep therapy [17].…”
Section: Introductionmentioning
confidence: 99%